Analisis Akuntansi Pendapatan Perpajakan dalam Rangka Penerapan Akuntansi Berbasis Akrual (Studi Kasus KPP Pratama Baubau) - Rudi Abdullah (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2017)
Accounting gets accrual basis will result more information akuntabel,  and transparent as compared to accounting gets cash basis. Accounting gets accrual basic can provide the better measurement, admitting that timely, and liabilities cast in the future. Information gets accrual basis can provide information about economic resource purpose that actually. This research intent to know accounting implement gets accrual basis accord PP 71 years 2010 on taxations propertied accounting. This observational type is observational kualitatif. Sample that is utilized is taxation propertied data on Taxeses Ministering Office Pratama Baubau year 2014. To show observational result that KPP Pratama Baubau has performed taxation income accounting with accrual basis bases prevailing order, which is PP 71 years 2010 and ruling supporting another. Taxation income is admitted while its appearance commanding rights on propertied taxation. Taxations propertied registry be performed according to Accounting Default journals Institutions. Taxations Propertied reporting KPP Pratama Baubau is presented in Budget Realization Reporting and Operational Reporting. This research result is expected Commanding that make ready qualified Man Resource optimal ala and ready deep implemented accounting gets accrual basis so will result qualified Government Financial Statement and gets can be accounted.Keywords: Taxation, Accounting income gets accrual basis